An inducible constitutive expression system in Bombyx mori mediated by phiC31 integrase. (10th September 2020) - Wang, Feng; Ji, Yan‐Ting; Tian, Chi; Wang, Yuan‐Cheng; Xu, Shen; Wang, Ri‐Yuan; Yang, Qian‐Qian; Zhao, Ping; Xia, Qing‐You
Abstract: Inducible gene‐expression systems play important roles in gene functional assays in the post‐genome era. Streptomyces phage‐derived phiC31 integrase, which mediates an irreversible site‐specific cassette exchange between the phage attachment site ( attP ) and the bacterial attachment site ( attB ), provides a promising option for the construction of a controllable gene‐expression system. Here, we report a phiC31 integrase‐mediated promoter flip system (FLIP) for the inducible expression of target genes in silkworm ( Bombyx mori ). First, we constructed a FLIP reporter system, in which a BmAct4 promoter with enhanced translational efficiency was flanked by the attB and attP sites in a head‐to‐head orientation and further linked in a reverse orientation to a DsRed reporter gene. The coexpression of a C‐terminal modified phiC31‐NLS integrase carrying a simian virus 40 (SV40) nuclear localization signal (NLS) effectively flipped the BmAct4 promoter through an attB / attP exchange, thereby activating the downstream expression of DsRed in a silkworm embryo‐derived cell line, BmE. Subsequently, the FLIP system, together with a system continuously expressing the phiC31‐NLS integrase, was used to construct binary transgenic silkworm lines. Hybridization between FLIP and phiC31‐NLS transgenic silkworm lines resulted in the successful flipping of the BmAct4 promoter, with an approximately 39% heritable transformation efficiency in silkworm offspring, leading to the constitutive and high‐level expression of DsRed in silkworms, which accounted for approximately 0.81% of the silkworm pupal weight. Our successful development of the FLIP system offers an effective alternative for manipulating gene expression in silkworms and other lepidopteran species. Abstract : Graphical Abstract The present study reports a phiC31 integrase‐mediated promoter flip system (FLIP) via the attB/attP exchange for the inducible expression of target genes in silkworms. Left inset illustrates the schematic of the FLIP system mediated by the phiC31 integrase‐induced attB/attP exchange. Right inset shows this system activates the efficient and inducible expression of DsRed in a silkworm embryo‐derived cell line BmE and silkworm individuals.